Parents Matter: A Descriptive Study of Parental Discussions With Teens About Violence Prevention and Related Topics - Edwards, Katie M. (Journal of interpersonal violence, 2022)
In the current article we examined the extent to which parents and caregivers engage in violence prevention and related discussions with their youth and the correlates (i.e., demographics, confidence, modeling of emotion regulation) of these experiences. We also examined the ways in which parents access prevention-related information to aid in these discussions with their youth. Participants were 142 parents/caregivers of a middle or high school-aged youth. Results suggested that adults reported speaking with youth about less sensitive prevention topics (e.g., bullying) more often than more sensitive topics (e.g., sexual violence). Whereas there were no demographic correlates for the level of confidence in discussing prevention topics with youth, emotion regulation modeling was positively correlated with confidence discussing prevention with youth. Also, parents who identified as White were less likely to discuss more sensitive topics with youth while parents who identified as American Indian were more likely to discuss more sensitive topics with youth and model emotion regulation. Having more confidence discussing prevention with youth positively correlated to discussing more sensitive and less sensitive topics with youth. These results underscore the need for engaging parents in prevention programming. More specifically, these data suggest that programs that builds parents? confidence and comfort in having prevention-related conversations with their youth, especially about more sensitive topics is needed in addition to programming that enhances parents? ability to model emotion regulation skills for their children.